Análise da expressão da β-Xilosidade II da bactéria aquática Caulobacter crescentus e seu papel no aproveitamento de resíduos agroindustriais. - Corrêa, Juliana Moço (2011)
Lignocellulosic materials are abundant in agro-industrial residues and by-products of agroindustry and can be used for fuels and other chemicals of commercial interest. An alternative to physical and chemical methods for bioconversion of lignocellulosic material is the use of enzymes produced by micro-organisms. The aquatic bacterium Gram negative Caulobacter crescentus presents biotechnological potential for the use of these residues because it contains in its genome several gene coding for enzymes involved in the metabolism of lignocellulosic materials, including 5 genes to β-Xylosidases. In this study, the gene xynB2 (1.5 kb) coding the C. crescentus β-Xylosidase II was cloned into the vector pJet1.2 (Fermentas) and subcloned in frame in the sites EcoRI/XbaI of expression vector pPROEXHta (Invitrogen). A histidine tail fusion protein was obtained after induction and expression of gene xynB2 in E. coli (DH10B) with IPTG (1 mM). The recombinant β-Xylosidase II (β-Xylrec- II) was purified by chromatography using nickel-Sepharose resin and a pure enzyme was characterized by biochemical kinetics parameters. A single band of 65 kDa was obtained by SDS-PAGE 9% for C. crescentus β-Xyl-rec-II purified, which showed a specific activity of 215 U / mg, pH optimum equal to 6, the optimum temperature of 55 °C and half life of 4 h at 50 °C. After 24 h incubation at pH 6 the enzyme retained 95% of activity. Most of the ions inhibited the activity of β-Xylosidase II, but a 32% increase was observed in the presence of KCl (2mM). The kinetic parameters KM and VMáx were equal to 8.4 mM and 370 moles / min, respectively. The ability of C. crescentus β-Xyl-rec-II hydrolyse xylan and sugarcane bagasse residue was assessed after incubation with these Xylanase purified from Aspergillus alliaceus. The relative percentage of hydrolysis products of xylan and sugar cane bagasse, increased 2.5 and 6.5 times, respectively, after incubation for 18 hours with C. crescentus β- Xyl-rec-II pure, thus highlighting the possibility of using this enzyme in biotechnological processes. In addition, β-Xil-rec-II was also used for the production of a polyclonal antibody in rabbit that showed by "Western blot" assay a highly specific recognition of the purified protein. In order to investigate the role of xynB2 gene to C. crescentus, two mutants were obtained. The first one was constructed by insertion of a spectinomycin resistance cassette into the xynB2 gene by double homologous recombination, generating a null mutant strain named RSJU-2. The second one was obtained by cloning of xynB2 gene under the control of the inducible xylose promoter generating a strain denominated pMOA. β-Xylosidase activity was measured in the RSJU-2, pMOA and parental strain (NA1000) cells of C. crescentus which were grown in the absence and in the presence of different agro-industrial residues and others carbon sources. The xynB2 gene depletion made cells more able to produce high activities of other β-Xylosidases in the presence of different residues, for instance, β- Xylosidase activity produced by RSJU-2 cells was almost 15 times higher than the activity showed by NA1000 in the presence of sugarcane bagasse. These results indicate that the absence o xynB2 gene up-regulates the expression of other β-Xylosidases in C. crescentus. On the other hand, a decreased activity of β-Xylosidase was observed in the strain pMOA, suggesting that the overexpression of β-Xylosidase II down-regulates C. crescentus β - Xylosidases activities. To verify that the variation in activity levels of β -Xylosidase occur as a consequence of variations in the levels of transcription of β-Xylosidases genes in different strains, we constructed a lacZ- fusion transcription by cloning the E. coli lacZ gene under the control of xynB2 gene promoter. Thus, the β-Galactosidase activity was measured as a function of xynB2 promoter activity. Tests of promoter activity by measuring the activity of β- Galactosidase in different strains showed that the xynB2 gene is transcription-dependent.